MANAJEMEN AIRTANAH PADA ENDAPAN ALUVIUM RAWA LAKBOK, JAWA BARAT - Hadian, Sapari Dwi; Rahmat, Bombom (Fakultas Teknik Geologi Universitas Padjadjaran, 2015)
Rawa Lakbok revealed as depression of Citanduy River, developed as peat swamp with type B overflow. Geographically, area of study located on 108° 35’ 29,3” – 108° 36’ 34,6” east longitude and 7° 23’ 33” – 7° 24’ 37, 7”south latitude. Area of study located on Puloerang Village, Sub-district of Lakbok, District of Ciamis, West Java. Geology success-ion of study area will be described in several aspect; Geomorphology, Stratigraphy, and Geological history. Geomorphologically, area of study consist of alluvium plain unit, and moderately steep volcanic unit From stratigraphy aspect, area of study consist of sandstone unit (Tpbp), Andesite unit (Tpa), and Alluvium unit (Qa). With Structural Geology heading South East – North West. Geological history of study area began in Early Pliocene with deposition of sand material. Afterwards, volcanic activity occurred and erupted andesite lava. At the end, alluvium was deposited as response of depression which formed in area of study.From the water balance calculation at Cibeber rivers area with width ± 10.12 kM2, known that : precipitation value 2,805.82 mM/Annual, 58.48% of pouring rain will evaporate, 21.11% will be run off, and 6.25% will infiltrate into the soil. Study area have 17.92% (5,088,437.2 M3/Annual) of axcess water of depression storage, means amount of water that accumulate in the surface of depression bowl from the study area surface run off. Hidrogeology of study area consist of hydraulic gradient values ranging from 0.0008 – 0.004. Hydraulic T Parameter ranging from 5 – 10 M2/day, K values ranging from 1 – 5 M/day, S value ranging from 1 – 5, and Sc value ranging from 17 – 37 M3/day/Mdd. Influence radius of Cone of depression rangingfrom 1.2–2 M. Keywords: depresion zone, groundwater manajemen